Orofacial functions - Linden, Frans P. G. M. van der, 1932-; Dentaurum (Firm) (Berlin ; Chicago : Quintessenz Verlag Neue Medien, 1999)
(Producer) Covers five areas: oral aspects of breathing, swallowing, and speaking; tooth eruption and movement; effect of occlusion on tooth position; equilibrium concepts regarding the dentition; and therapeutic procedures for abnormal oral behavior.
Author, Frans P.G.M. van der Linden, with the asistance of William R. Proffit ; scientific contributions, Rainer R. Miethke, et al ; script, Frans P.G.M. van der Linden, with the asistance of William R. Proffit
Keywords: Stomatognathic System -- physiology; Dental occlusion; Tooth -- growth & development